Perbandingan Besar Gaya Gesek Kawat Busur Rektangular stainless steel pada Braket Logam antara Teknik - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
During ortodhontic tooth movement, friction generated at the brakes and archwire interface tends to impede the desired movement. The ligation technique is an important contributor to this frictional force. The purpose of this study was to investigate the comparison of frictional forces stainless steel rectanguler wire on metal bracket between ligation technique ligature wire and elastomeric. Objects consisted of 30 Edgewise orthodontic bracket 0.018x0.022 inchi combination with 0.016x0.016 inchi stainless steel rectanguler wire. Fifteen combination were ligated with ligature wire and 15 combination were ligated with elastomeric ligature. Frictional forces is the force needed to start movement. Frictional forces measured with universal testing machine with gram. Student West was used to compare frictional forces stainless steel rectanguler wire on metal bracket between ligation technique ligature wire and elastomeric. The result showed that frictional forces stainless steel rectanguler wire on metal bracket with ligation technique ligature wire produced lower friction compared with ligature elastomeric, and has significant differences (p